Answer:
-256/9 or -28.4
Step-by-step explanation:
-1/3 / 3/5 = -1/3 x 5/3 = -5/9
-29 - -5/9 = -261/9 + 5/9 = -256/9 or -28.4
Answer:
A) 2 + i
Step-by-step explanation:
F(x) = x^3 - 3x^2 + x + 5
0 = x^3 - 3x^2 + x + 5
0 = (x+1)(x^2 - 4x + 5)
Great, now we can separate these two parenthesis expressions because of the Zero Product Property. Start with the simple one:
0 = x + 1
<u>x = -1</u>
We have our first real root! But it doesn't look like that's one of the answer choices, so move on to the other expression:
0 = (x^2 - 4x +5)
This expression can't be factored, so we will use the quadratic formula (which is x = ).
First solve for the positive part:
= (4 + sqrt(16-20)) / 2
= 4 + sqrt(-4) / 2
= 4 + 2i / 2
<u>= 2 + i</u>
Then for the negative part:
= (4 - sqrt(16-20)) / 2
= 4 - sqrt(-4) / 2
= 4 - 2i / 2
<u>= 2 - i</u>
<u></u>
<u>2 + i</u> is answer choice A! Our other roots, <u>2 - i</u> and <u>-1</u>, aren't answer choices.
Answer:
1/3
Step-by-step explanation:
3^2/5 x 3^-7/5
We know that a^b* a^c = a^(b+c)
3^(2/5 -7/5)
3^ (-5/5) = 3^ -1
We know that a^-b = 1/ a^b
3^-1 = 1 / 3
Answer:
She now has 84 nickles. :)
Step-by-step explanation:
40+44=84